Nutritional Hygiene of Preschoolers in Russian Metropolitan Noble Families of the Intelligentsia in the late XIX - early XX Centuries - Valentina A. Veremenko; Julia V. Sutula (RUDN Journal of Russian History, 2023)
Through their article, the authors have conducted research on the suggested requirements for the nutrition of preschoolers which were established at the turn of the XX century in Russia, as well as on their implementation within noble intelligentsia families. The source base of the article includes the works of hygienists and nutritionists, reports of sanitary and pedagogical organizations, journalism, home economics guidelines, as well as ego documents. It is shown within these text that the idea of the importance of a proper diet for children as a way for them to obtain the necessary vitamins and minerals for the “building” of their body, and maintaining health had the greatest resonance with intelligent metropolitan female residents who had both the opportunity and desire to get acquainted with the latest scientific achievements in this field. The authors provide a conclusion that not only parents’ willingness to apply ideas from the guidelines instrumental in this process, but also guided the extreme difficulty of implementing them in practice, even in “responsible” families. The abundance and inconsistency of the recommendations combined with the difficulties of their implementation and additional financial and labor costs often forced women to adapt the ideas of nutritionists to the available opportunities of the time and their own ideas. As a result, even in “responsible” noble intelligent families, there could be bizarrely combined various, sometimes mutually exclusive, nutritional practices for preschoolers.